Calling the shots: Young professional women's relationship with alcohol. (May 2015) - Watts, Rosalind; Linke, Stuart; Murray, Elizabeth; Barker, Chris
Alcohol consumption by young professional women is increasing. Whilst the media and public health campaigns have condemned this increase, societal attitudes and advertising discourses frame it as a display of "power femininity". This qualitative study explored young professional women's "relationship with alcohol": why they drank and how they felt about it. Twelve young professional women who reported drinking over official limits and had not sought professional help were recruited via UK public houses (drinking establishments, usually called pubs) and later interviewed. Transcripts were analysed thematically. Participants used alcohol to gain power; they saw drinking as a masculine ability demonstrating stamina, valued professionally and socially. However, women were also ashamed of their drinking; they felt criticised by health professionals and the media. Rather than perpetuating a blaming and shaming discourse, it may be important to counteract social norms associating alcohol use with power and sobriety with weakness.